TESTING AND EVALUATION OF KNOWLEDGE, SKILLS AND SKILLS OF STUDENTS IN CLASS GEOMETRY AND ENGINEERING GRAPHICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
To take general approaches by analyzing the developments used in the practice of correct assessment of knowledge, skills and abilities of students in the lessons of descriptive geometry and engineering graphics.